2009
DOI: 10.1007/s00787-009-0747-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of transitional object use in adolescence: is there a connection between the existence of a transitional object and depressive symptoms?

Abstract: Objective: The purpose of the study was to investigate the prevalence of the use of a transitional object (TO) in adolescence and its connection with depressive symptoms and mental distress in youth by gender. Method: The study group consisted of 1,054 adolescents (465 boys, 589 girls) from normal comprehensive schools in Turku, a Finnish town with approximately 175,000 inhabitants. The mean age of both gender groups was 14.5 years (SD 0.5); respondents came from all social classes. Background and TO informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
3
10
0
2
Order By: Relevance
“…Mental distress increases physical symptoms, such as headache, stomach pain, and musculoskeletal aches, and vice versa. In the whole study group, girls had 2.67-times higher odds to be TO users in adolescence, which is in line with the results of our former study (10). The odds for adolescents with frequent pain and aches to be TO users were 1.59-times higher in the whole study group, 1.96-times higher in boys, and 1.65-times higher in girls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mental distress increases physical symptoms, such as headache, stomach pain, and musculoskeletal aches, and vice versa. In the whole study group, girls had 2.67-times higher odds to be TO users in adolescence, which is in line with the results of our former study (10). The odds for adolescents with frequent pain and aches to be TO users were 1.59-times higher in the whole study group, 1.96-times higher in boys, and 1.65-times higher in girls.…”
Section: Discussionsupporting
confidence: 93%
“…In general adolescent populations, adolescents showing attachment to a TO have been reported as having significantly more psychiatric symptoms and poorer general well-being than non-users (10)(11)(12). There are also clinical notions about the importance of TOs and other transitional phenomena during adolescent years when issues around one's bodily changes and identity become major developmental tasks (10)(11)(12)(13). Subjects who had an imaginary companion in childhood displayed prolonged TO attachment and more immature modes of coping with stress (14).…”
Section: Introductionmentioning
confidence: 99%
“…Cohen & Clark, 1984). Given the high frequency of the comfort objects in adolescence (Erkolahti & Nyström, 2009) and that 30% of the participants of this study had their comfort object with them in college, the relevance of the present results is enhanced. Nonetheless, future research should aim at replicating these findings in children.…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, attachment to hard objects such as toys and bottles appeared to be low in intensity and less likely to change than the attachment to soft objects did (Passman & Halonen, 1979). The use of comfort objects was common in adolescence too as Erkolahti and Nyström (2009) reported that 29% of the 14 -15-year-olds had such objects, with girls having significantly more soft objects than boys who preferred hard toys.…”
mentioning
confidence: 88%
“…Sherman, Hertzig, Austrian, and Shapiro (1981) reported that 54% of children from New York schools had a transitional object in infancy, and 49% of transitional object users had kept their transitional object until the age of 9. Further studies have reported that between 22 and 29% of adolescents retain transitional objects (Bachar, Canetti, Galilee-Weisstub, Kaplan-DeNour, & Shalev, 1998;Erkolahti & Nystr€ om, 2009;Shafii, 1986). Gender also plays a role in transitional object use in adolescence, with more girls than boys reporting transitional object use (Erkolahti & Nystr€ om, 2009;Shafii, 1986).…”
mentioning
confidence: 98%